Effect of Concentration of Catalyst (BF3-Diethyl Etherate) on Synthesis of Polyester From Palm Fatty Acid Distillate (PFAD) - Renita Manurung; Ahmad Rozi Tanjung; Ida Ayuningrum (International Journal of Science and Engineering, 2013)
Palm Fatty Acid Distillate (PFAD) can be used as raw material for synthesis polyester. The aim of this research is to synthesis of polyester and to determine the effect of concentration of catalyst on polymerization methyl ester PFAD. The esterification stage was done at temperature 70oC, reaction time 120 minute, reactant ratio 1:8 (PFAD: methanol), concentration of catalyst (H2SO4) 1% (w/w) PFAD; polymerization stage was done at temperature 126-132°C, polymerization reaction time 4 hours; variation of concentration of catalyst (BF3-diethyl etherate) 0%, 6.9%, 9.2%, 11.5% (w/w) methyl ester; and polyesterification stage was done at temperature 175-200 oC, reactant ratios (w/w) 1:1 (polymerized ME : ethylene glycol), reaction time 4 hours and all of stage was stirred at 150 rpm. The results showed, in the esterification stage was obtained methyl ester with iodine value 77.29 g I2/100 g, viscosity 6.90 cP, density 859.91 kg/m3 and analysis by using GC-MS showed that the purity of methyl ester was 82.23% and molecular weight 267.97 g/mol. Decreasing in iodine value from 77.29 I2 g/100 g to 74.97-59.99 g I2/100 g indicated that the polymerization process had taken place. In polyesterification stage was obtained light brown colored liquid for concentration of catalyst 0%; viscous, light brown colored liquid for concentration of catalyst 6.9%; and gel polyester, viscous, dark brown colored solid at room temperature for concentration of catalyst 9.2% and 11.5% with acid value from 8.19 to 26.14 mg KOH/g, viscosity from 0.07 to 15.2 P, and molecular weight 288.81 to 1522.07 g/mol which is more suitable for applications of modified polyester. Analysis by using GC showed that the purity of polyester is equal to 65.49%. Keywords— polyester, palm fatty acid distillate, polymerizationconcentration of catalyst,biodegradable polymer